'A sword of Damocles': patient and caregiver beliefs, attitudes and perspectives on presymptomatic testing for autosomal dominant polycystic kidney disease: a focus group study. Issue 10 (10th October 2020) - Logeman, Charlotte; Cho, Yeoungjee; Sautenet, Benedicte; Rangan, Gopala K; Gutman, Talia; Craig, Jonathan; Ong, Albert; Chapman, Arlene; Ahn, Curie; Coolican, Helen; Tze-Wah Kao, Juliana; Gansevoort, Ron T; et al.
Abstract : Background and objectives: Presymptomatic testing is available for early diagnosis of hereditary autosomal dominant polycystic kidney disease (ADPKD). However, the complex ethical and psychosocial implications can make decision-making challenging and require an understanding of patients' values, goals and priorities. This study aims to describe patient and caregiver beliefs and expectations regarding presymptomatic testing for ADPKD. Design, setting and participants: 154 participants (120 patients and 34 caregivers) aged 18 years and over from eight centres in Australia, France and Korea participated in 17 focus groups. Transcripts were analysed thematically. Results: We identified five themes: avoiding financial disadvantage (insecurity in the inability to obtain life insurance, limited work opportunities, financial burden); futility in uncertainty (erratic and diverse manifestations of disease limiting utility, taking preventive actions in vain, daunted by perplexity of results, unaware of risk of inheriting ADPKD); lacking autonomy and support in decisions (overwhelmed by ambiguous information, medicalising family planning, family pressures); seizing control of well-being (gaining confidence in early detection, allowing preparation for the future, reassurance in family resilience); and anticipating impact on quality of life (reassured by lack of symptoms, judging value of life with ADPKD). Conclusions: For patients with ADPKD, presymptomatic testing provides an opportunity to take ownership of their health through family planning and preventive measures. However, these decisions can be wrought with tensions and uncertainty about prognostic implications, and the psychosocial and financial burden of testing. Healthcare professionals should focus on genetic counselling, mental health and providing education to patients' families to support informed decision-making. Policymakers should consider the cost burden and risk of discrimination when informing government policies. Finally, patients are recommended to focus on self-care from an early age.